Prevalence, clinical features and outcomes of neonatal Covid-19 infection at a tertiary center in Turkey - Yarci, Erbu; Bozdemir, Sefika Elmas (Annals of Medical Research, 2022)
Aim: Newborns constitute a special and sensitive group within the pediatric age group due to their unique characteristics and disease. We evaluated the prevalence, clinical features and outcomes of neonates admitted to emergency department and hospitalized with suspected SARS-CoV-2 infection. Materials and Methods: In this retrospective, single centre study all neonates admitted to emergency department with suspected SARS-CoV-2 infection between March 11, 2020 and March 11, 2021 were enrolled. Results: Fifty-five newborns were hospitalized in (Neonatal Intensive Care Unit) NICU with a suspicion of SARS-CoV-2 infection during the study period. PCR was positive in 14 newborns out of 55 hospitalized newborns (25.5%). Thirteen (92.8%) newborns with a positive SARS-CoV-2 PCR had household contact. The most common findings on admission were fever (43%), feeding intolerance (29%) and tachypnea (14%). One (7%) newborn was asymptomatic on admission. Three newborns (21%) had lymphopenia. Seven (50%) newborns had leukopenia, but none of them had neutropenia. D-dimer levels of nine (64%) SARS-CoV-2 positive newborns were elevated but none of these patients had coagulation disorders or problems needing treatment. Five of fourteen PCR positive newborns (35%) needed suplemental oxgen, while a newborn baby (7%) neeeded non-invasive mechanical ventilation. Conclusions: Fever is a common symptom in SARS-CoV-2 infected newborns but new symptoms will be encountered in the course of the pandemics. Clinical information and course of SARS-CoV-2 in newborns has an obscurity. In the pandemic conditions all newborns, especially having a contact with a SARS-CoV-2 infected person must be tested for SARS-CoV-2 even if having no symptoms.
Keywords: Covid-19; newborn; outcome; prevalence